Postpartum anhedonia: Emergent patterns in bipolar and unipolar depression. (December 2021) - Gollan, Jacqueline K; Yang, Amy; Ciolino, Jody D.; Sit, Dorothy; Wisner, Katherine L.
Highlights: Course trajectories of anhedonia across postpartum is unknown. Anhedonia is reported in twice as many women with bipolar relative to unipolar depression. Chronic postpartum anhedonia higher in women with bipolar than unipolar depression. Abstract: The objective of this study was to identify differences in the longitudinal course anhedonia symptoms during postpartum in women diagnosed with unipolar or bipolar disorder. Female participants diagnosed with either bipolar ( n = 104) or unipolar ( n = 136) depression at week 20 during pregnancy were evaluated prospectively at weeks 2, 12, 26, and 52 postpartum using clinical interviews. A semi-parametric, group-based mixture model was applied to separate distinct longitudinal patterns of symptoms of anhedonia. Across time, among those who reported anhedonia, twice as many women had the diagnoses of bipolar depression relative to unipolar depression (65.03% versus 39.47%, respectively). Moreover, the rate and stability of anhedonia was higher in women with bipolar relative to unipolar depression. Across groups, anhedonia was associated with significantly higher depressive symptom severity. Anhedonia is a more stable and frequent symptom in women with postpartum bipolar relative to unipolar depressive disorder.